PENGEMBANGAN BAHAN AJAR DRAMA BERBANTUAN CANVA DI SMA NEGERI 2 MEDAN - Tiana Silalahi; Nurul Azizah; Trisnawati Hutagalung; Eskawana Nababan; Salamah; Hikmah Tiar Simanjuntak; Yana Melia Sari Sipayung; Yuni Asri Nur Ain Lubis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop valid, practical, and effective Canva-based drama teaching materials to improve high school students' understanding of drama elements, performance skills, and learning motivation. The research method used is Research and Development (R&D) with the ADDIE model. The research subjects are 11th grade students at SMA Negeri 2 Medan and Indonesian language teachers. The data analysis technique used was qualitative data analysis with the Miles Huberman and Saldana model, including data reduction, data presentation, and conclusion drawing. The results showed that Canva-based teaching materials were effective in improving students' understanding of drama concepts, practical skills (such as script writing and performance), and affective aspects (such as confidence and cooperation). The use of Canva as a digital learning medium made it easier for teachers and students to access materials visually and interactively.